The Reef Check Mediterranean Underwater Coastal Environment Monitoring Protocol - Turicchia, Eva; Ponti, Massimo; Rossi, Gianfranco; Milanese, Martina; Di Camillo, Cristina Gioia; Cerrano, Carlo (Frontiers in Marine Science, 2021)
Since 2001, trained snorkelers, freedivers, and scuba diver volunteers (collectively called EcoDivers) have been recording data on the distribution, abundance, and bathymetric range of 43 selected key marine species along the Mediterranean Sea coasts using the Reef Check Mediterranean Underwater Coastal Environment Monitoring (RCMed U-CEM) protocol. The taxa, including algae, invertebrates, and fishes, were selected by a combination of criteria, including ease of identification and being a key indicator of shifts in the Mediterranean subtidal habitats due to local pressures and climate change. The dataset collected using the RCMed U-CEM protocol is openly accessible across different platforms and allows for various uses. It has proven to be useful for several purposes, such as monitoring the ecological status of Mediterranean coastal environments, assessing the effects of human impacts and management interventions, as well as complementing scientific papers on species distribution and abundance, distribution modeling, and historical series. Also, the commitment of volunteers promotes marine stewardship and environmental awareness in marine conservation. Here, we describe the RCMed U-CEM protocol from training volunteers to recording, delivering, and sharing data, including the quality assurance and control (QA/QC) procedures.